What does currency order flow tell about spot exchange rates of Asian emerging markets? - Muhammad, Aftab; Anifowose, Abolaji Daniel; Lau, Evan Poh Hock; Izlin, Ismail (Elsevier B.V., 2020)
This study investigates the role of currency order flow in explaining the emerging Asian markets'exchange rates relying on linear andnonlinear modeling. The daily currency order flow of the US dollar relative to the nine important Asian currencies is constituted and exploredwith the respective exchange rates. First, we find that order flow affects the spot exchange rate positively for the sampled Asian currencies whichindicates that the buying pressure of the US dollar depreciates Asian currencies. Second, the effect of order flow is asymmetric which explainsthat a surge and a fall in order flow have different effects on the exchange rate. This study unlocks the contribution of the market microstructureresearch where the asymmetries improve the power to explicate exchange rates. The nonlinear model forecasting performance validates thisstance.